Development of Patient-Derived Human Monoclonal Antibodies Against Nucleocapsid Protein of Severe Acute Respiratory Syndrome Coronavirus 2 for Coronavirus Disease 2019 Diagnosis - Zhang, Li; Zheng, Binyang; Gao, Xingsu; Zhang, Libo; Pan, Hongxin; Qiao, Yong; Suo, Guangli; Zhu, Fengcai (Frontiers in Immunology, 2020)
The pandemic caused by emerging Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) presents a global public health threat. Illustrating human antibody responding to viral antigen could potentially provide valuable information for basic research and clinical diagnosis. Antibodies can be used as complement to the viral detection for rapid diagnosis of infected patients. Compared with spike protein (SP), nucleocapsid protein (NP) is normally conserved and highly immunogenic in many members of coronavirus. As a major antigen, NP is a potential target for diagnosis of SARS-CoV-2 infection. Here, we constructed a combinatorial Fab antibody phage library based on peripheral blood derived from five coronavirus disease 2019 (COVID-19) infected donors. From the library, 159 Fab antibodies were obtained and identified by panning with NP. Among them, 16 of antibodies were evaluated for their binding properties and epitopes recognition. Among these 16 antibodies, two well-paired antibodies were finally screened out for the purpose of SARS-CoV-2 diagnosis by double-antibody sandwich ELISA method. Our works may provide potential resource for clinical diagnosis of SARS-CoV-2 infection.